An Implementation of a Crime-Safety-Map Application Based on a Safety Index - Seong-Cho Hong; Svetlana Kim; Sun-Young Ihm (Multimodal Technologies and Interaction)
This paper presents the development of a crime-safety-map application and a safety index using the heatmap and geofence methods. The need for a tool that can satisfy safety needs has become more important than ever due to society’s growing fear of crime. One way to satisfy the general public’s safety needs is by informing them of crime data and the safety level of the surrounding environment, but it is not disclosed by law enforcement agencies. Therefore, this study focused on crime prevention through environmental design for developing a user-friendly, open to the public crime-safety-map application. Data from the Republic of Korean Open Government Data Portal’s nationwide safety and crime related data were used and the application was designed using Android Studio. The developed application visualizes the characteristic of the surrounding environment and can also inform crime safety level through a heatmap and the geofence technique. This application can reduce the general public’s fear of crime and crime incidents by informing and warning them about the crime prone areas.